ANALISIS PENYEBAB PEKERJAAN PERBAIKAN PENGECORAN PROYEK X DENGAN PARETO CHART - Ryobi Irfanto (Universitas Kristen Maranatha, 2022)
Construction projects are inseparable from their unique management. The unique management of construction projects makes it difficult to maintain their quality. One of the tools to measure quality in project management is the Pareto chart. Pareto chart is a statistical technique that is usually used for decision making based on the frequency of events compared to the causes of events. This research was conducted to analyze the causes of repair work on project X by using Pareto chart. The conceptual framework used in this study is based on two approaches, namely literature and field observations. The main literature for analysis is the Pareto chart then field data collection on each component first which is then categorized based on the type of work. After the data is categorized, a Pareto chart will be made from the data. The processing results obtained two dominant types of errors in the casting work, namely cracks and unevenness of the casting results. Cracks and unevenness of the casting results can be overcome by the chipping method then followed by grouting if necessary. The chipping method is used to repair porous concrete or flatten the casting if it swells, and the grouting method to fill cracks and chipping results with a mixture of cement and water until the surface becomes flat and the casting work results are better.